Crohn's Disease in Children: A Case Report - Nuraini Irma Susanti; Nicodemus Nicodemus (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2023)
Background: Crohn's disease in children is a chronic inflammatory bowel disease (IBD). The incidence of this disease has tended to increase in recent decades. This case report aimed to increase clinician insight into Crohn's disease. Case: We reported a case of Crohn's disease, one of the inflammatory bowel disease (IBD) type in a 16-year-old boy. The patient came with complaints of loose stools without mucus and blood, accompanied by heartburn, nausea, vomiting, and decreased appetite. The patient had a history of changes in defecation patterns in the last 4 months and decreased appetite and weight loss in the last 1 month. There was epigastric tenderness on physical examination. Inflammatory markers and fecal calprotectin values were increased. Gastrointestinal endoscopy results found pangastritis and pancolitis with histopathological examination showing results appropriate to IBD. The patient received corticosteroid methylprednisolone 1 mg/kg/day as induction therapy and experienced improvement in symptoms and laboratory results after 7 days of therapy. Discussion: There are characteristic differences between Crohn's disease and ulcerative colitis. A definite diagnosis is made by endoscopy and histopathological examination. The current goal of Crohn's disease therapy is no longer limited to improving symptoms or optimizing growth and development, but also targeting the improvement of the gastrointestinal mucosa. Remission induction therapy can be carried out with exclusive enteral nutrition or corticosteroids which are gradually reduced. Conclusion: This case report increases clinician insight into the characteristics, approaches to IBD diagnosis, and remission induction therapy in Crohn's disease in children.